PENGARUH STRATEGI PENGEMBANGAN PEMASARAN PENGRAJIN BATIK TERHADAP PENINGKATAN PENJUALAN BATIK SINGKUT DI DESA BUKIT MURAU KECAMATAN SINGKUT KABUPATEN SAROLANGUN - Redi Indra Yudha, Wiwin Kurniasih (Universitas Batanghari Jambi, 2019)
Abstract This study aims to determine (1) To determine the utilization of marketing development strategies in increasing batik sales in the Bukit Murau Village, Singkut District, Sarolangun Regency. (2) To determine the effect of the use of marketing development strategies to increase sales of batik products in the Bukit Murau Village, Singkut District, Sarolangun Regency. This research design uses survey research with quantitative methods. Meanwhile, the population in this study were 35 batik artisans in Bukit Murau village, while the sample in this study was in accordance with the large population because the population in this study was less than 100. The results showed that (1) The results of the marketing strategy manual calculation got a TCR value of 82.15%, so that it was in the good category. Meanwhile, the increase in sales got a TCR value of 82.2%, so that it is in the good category. (2) After being tested persially (t test) the testing of the marketing strategy hypothesis shows the t value of 8.295 or positive with a significant level of 0.009. Then t arithmetic> T table (8.295> 0.05) and the significance level is less than 0.05 (0.009 <0.05), which means that the hypothesis in this study rejects Ho and accepts Ha. Keywords : Marketing Development Strategy and Sales Increase